Ojek dari Masa ke Masa Kajian secara Manajemen Sumber Daya Manusia - Fauziah, Neneng (JURNAL ADMINISTRASI DAN KEBIJAKAN PUBLIK, 2017)
The fulfillment of the need for transportation with conventional motorcycle taxis or online, the good and bad of each transportation is reasonable if then many users/passengers motorcycle taxis to switch to online motorcycle taxis, but also unfair if the traditional motorcycle are rampant/hostile to online motorcycle taxis. Better Online motorcycle taxis they follow the management of modern motorcycle taxis to still/continue exist. Traditional motorcycle taxis will be abandoned/left by passengers/users, as passenger/users will be looking for more pratical and cheap, traditional motorcycle taxis driver can’t control passengers.Prosession as motorcycle taxis driver became one of the solution to reduce the unemployed rate when viewed from the point of view of MSDM, which is earning income, does’t require special skill it only takes discipline and perseverance in performing their duties.